Dementia with Lewy bodies can be well‐differentiated from Alzheimer's disease by measurement of brain acetylcholinesterase activity—a [11C]MP4A PET study. (17th August 2015) - Shimada, H.; Hirano, S.; Sinotoh, H.; Ota, T.; Tanaka, N.; Sato, K.; Yamada, M.; Fukushi, K.; Irie, T.; Zhang, M. R.; Higuchi, M.; Kuwabara, S.; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate the diagnostic performance of brain acetylcholinesterase (AChE) activity measurement using N‐[11C]‐methyl‐4‐piperidyl acetate (MP4A) and PET in patients with dementia with Lewy bodies (DLB) and Alzheimer's disease (AD). Methods Participants were 14 DLB patients, 25 AD patients and 18 age‐matched healthy controls (HC). All subjects underwent PET scans and MP4A to measure regional brain AChE activity. We performed anatomical standardization of each brain image, and k3 values, an index of AChE activity, in each voxel were estimated by nonlinear least squares analysis. Volumes of interest (VOIs) were identified on parametric k3 images in frontal, temporal, parietal and occipital cortices, and in anterior and posterior cingulate gyri (ACG and PCG). In each VOI, the differential diagnostic performance between AD and DLB of k3 values was assessed by area under the curve (AUC) of the receiver‐operating characteristic. Voxel‐based statistical analyses were also performed. Results Mean cortical AChE activities in AD patients (−8.2% compared with normal mean) and DLB patients (−27.8%) were lower than HCs (p < 0.05, p < 0.001, respectively). There was a significant difference in mean cortical AChE activities between AD and DLB patients (p < 0.001). All regional brain AChE activities of defined VOIs except ACG were able to well discriminate DLB from AD, and notably performance was the most significant in PCG (AUC = 0.989, 95% CI: 0.965–1.000). Conclusions Brain cholinergic deficit is consistently prominent in DLB compared with AD. PET measurement of brain AChE activity may be useful for the differential diagnosis between DLB and AD. Copyright © 2015 John Wiley & Sons, Ltd.